2020
DOI: 10.3389/fphar.2020.01228
|View full text |Cite
|
Sign up to set email alerts
|

Cavin3 Suppresses Breast Cancer Metastasis via Inhibiting AKT Pathway

Abstract: Objective: Cavin3 is a putative tumor suppressor protein. However, its molecular action on tumor regulation is largely unknown. The aim of the current study is to explore the implication of cavin3 alteration, its clinical significance, and any potential molecular mechanisms in the regulation of breast cancer (BC). Methods: TCGA (The Cancer Genome Atlas) and GTEx (Genotype-Tissue Expression) data bases, and 17 freshly paired BC and adjacent normal tissues were analyzed for mRNA levels of Cavin3. Furthermore, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Loss of cavin3 expression is more prevalent in late-stage/high-grade cancers than in early-stage/low-grade cancers ( An et al, 2020 ; Carén et al, 2011 ; Lee et al, 2008 ; Wikman et al, 2012 ). Cavin3 expression is lost due to promoter methylation in numerous cancer types ( Lee et al, 2008 ; Lee et al, 2011 ; Martinez et al, 2009 ; Tong et al, 2010 ; Xu et al, 2001 ; Zöchbauer-Müller et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of cavin3 expression is more prevalent in late-stage/high-grade cancers than in early-stage/low-grade cancers ( An et al, 2020 ; Carén et al, 2011 ; Lee et al, 2008 ; Wikman et al, 2012 ). Cavin3 expression is lost due to promoter methylation in numerous cancer types ( Lee et al, 2008 ; Lee et al, 2011 ; Martinez et al, 2009 ; Tong et al, 2010 ; Xu et al, 2001 ; Zöchbauer-Müller et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of cavin3 expression is more prevalent in late-stage/high-grade cancers than in earlystage/low-grade cancers (An et al, 2020;Caren et al, 2011;Lee et al, 2008;Wikman et al, 2012).…”
Section: /06/21mentioning
confidence: 99%
“…Identifying metastasis-associated genes and finding effective targets is the main strategy to prevent metastasis and improve survival of breast cancer. On the explore of putative tumor suppressor protein, Xin An et al ( An et al, 2020 ) confirmed that Cavin3 expression is significantly downregulated in breast cancer, and correlated with distant metastasis and worse survival. Cavin3 functions as a metastasis suppressor by downregulating the Akt pathway, which suggests that cavin3 can be a potential prognostic biomarker and a target for breast cancer treatment.…”
mentioning
confidence: 99%